Estructuración Del Periodismo Ambiental En Medios Impresos: Hacia Una Visión Compleja (2012)
The article is extracted from research whose aim was to analyze the structuring of environmental journalism for print media in the State of Falcon, with a tendency to manage using a complex vision. In Venezuela, the press almost always reflects content of events and disasters, highlighting the journalist as the modeler of his source, not in the active, intermediary role of building an environmental culture. The research is descriptive, with a non-experimental, field design, based on environmental journalism theories. A population census of 39 journalists working at newspapers in the State of Falcon was established. Results showed that environmental issues have a low profile and are not part of the policies established for newspapers in Falcon. It is suggested that journalists be trained in order to construct an agenda and insert environmental issues in the platform and to build environmental citizenship.